1998
DOI: 10.1046/j.1523-1755.1998.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive treatment of patients with proteinuric renal diseases: Risks or benefits of calcium channel blockers?

Abstract: In patients with proteinuric renal diseases the rate of progression of renal insufficiency is determined by the level of blood pressure and proteinuria. It has been demonstrated that strict blood pressure control with angiotensin converting enzyme (ACE)-inhibitors or beta-blockers, aimed at reaching values below 130/80 mm Hg, attenuates the deterioration of renal function. In general, the beneficial effects of these drugs are reflected in a parallel lowering of proteinuria. Calcium channel blockers are effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 131 publications
(52 reference statements)
4
66
0
1
Order By: Relevance
“…Similar relationships between impaired renal autoregulation and increased renal susceptibility to hypertensive injury have been noted in the DOCA/salt model of hypertension (72,109), and in the nonclipped kidney of the 2K/1C model (124,133). Moreover, interventions that alter autoregulatory capacity, such as dietary protein restriction or calcium channel blockers, produce corresponding changes in susceptibility to hypertensive injury in models of CKD (57,60,62) and in the DOCA/ salt and 2K/1C models of hypertension (92,133).…”
Section: Consequences Of Impaired Renal Autoregulation On Renal Protesupporting
confidence: 54%
“…Similar relationships between impaired renal autoregulation and increased renal susceptibility to hypertensive injury have been noted in the DOCA/salt model of hypertension (72,109), and in the nonclipped kidney of the 2K/1C model (124,133). Moreover, interventions that alter autoregulatory capacity, such as dietary protein restriction or calcium channel blockers, produce corresponding changes in susceptibility to hypertensive injury in models of CKD (57,60,62) and in the DOCA/ salt and 2K/1C models of hypertension (92,133).…”
Section: Consequences Of Impaired Renal Autoregulation On Renal Protesupporting
confidence: 54%
“…However, the effects of CCBs on renal diseases drawn from current the available clinical data are quite contradictory: beneficial, neutral, even adverse. [6][7][8] To assess the action of CCBs on the progression of CKD, we undertook a systematic review and meta-analysis of clinical randomized controlled trials investigating the effects of CCBs on renal outcomes and all-cause mortality compared with ACEIs or ARBs.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors of L-type channels are often used in treatment of hypertension and it has been suggested that this leads to increased glomerular capillary pressure due to loss of renal autoregulation leading to increased proteinuria and glomerulosclerosis. 95,96 Therefore focus has increased on the role of T-type channels in renal protection 97,98 as they are hypothesized to reduce glomerular pressure.…”
Section: Renal Autoregulationmentioning
confidence: 99%